2021
DOI: 10.1002/jum.15866
|View full text |Cite
|
Sign up to set email alerts
|

A Meta‐Analysis of Analgesic Effect of Ultrasound Therapy for Patients With Knee Osteoarthritis

Abstract: To compare the efficacy of therapeutic ultrasound in pain relief and functional recovery in knee osteoarthritis. A comprehensive search of five databases including EMBASE, PubMed, CBM, the Cochrane Library, and Google scholar was conducted to identify relevant studies published between January 1, 2005 and December 31, 2020. Eligible randomized trials were screened for inclusion in this study. Data about the mean change of visual analogue scale (VAS), Western Ontario and McMaster Universities Osteoarthritis Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…A subgroup analysis of 2 different US models performed by Liu 2022 [ 18 ] showed that both pulsed and continuous therapeutic US were effective in relieving pain. In addition, a direct comparison between pulsed US and continuous US was also performed, showing no significant difference between the two modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subgroup analysis of 2 different US models performed by Liu 2022 [ 18 ] showed that both pulsed and continuous therapeutic US were effective in relieving pain. In addition, a direct comparison between pulsed US and continuous US was also performed, showing no significant difference between the two modalities.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the evidence found that the analgesic and functional effects of US on KOA are inconclusive [ 13 ]. Previous systematic reviews on the effectiveness of US in the treatment of KOA are outdated [ [14] , [15] , [16] , [17] , [18] , [19] , [20] ], and even the latest meta-analysis [ 18 ] published in 2022, only included trials up to December 2020, and the quality of the included trials was poor. Some systematic reviews and meta-analyses only studied the efficacy analysis of low-intensity US therapy or pulsed US for KOA and did not include other types of US [ [21] , [22] , [23] ], some only compare therapeutic US with sham US (or no intervention) without considering concurrent treatment [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low-intensity pulsed ultrasound (LIPUS) is a noninvasive therapeutic approach that has been used for several years as a supplement for bone healing. Usually, LIPUS treatment for bone repair is applied once daily by using a transducer placed on the surface of the skin over the fracture site [3]. The tissue repair effect of LIPUS is primarily attributed to its mechanical and thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…The tissue repair effect of LIPUS is primarily attributed to its mechanical and thermal properties. The main therapeutic effect of LIPUS results from its mechanical effects [3]. The propagation of LIPUS through the medium causes the movement of substances, which produces a massage effect on cells in the medium [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the commented article, 1 we identified the standardized mean difference (SMD) had been used to quantify the outcome. The SMD is derived from the between-group difference in means divided by the pooled standard deviation.…”
mentioning
confidence: 99%